2022
DOI: 10.1111/bcp.15531
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding events among patients concomitantly treated with direct oral anticoagulants and macrolide or fluoroquinolone antibiotics

Abstract: Fluoroquinolones and macrolides may, due to a potential drug‐drug interaction, increase the concentration of any concomitantly administered direct oral anticoagulant (DOAC) and thereby increase the risk of severe bleeding. However, clinical evidence for such an effect is scarce. The present study aimed to evaluate the association between the use of fluoroquinolones or macrolides and bleeding events in patients with concomitant DOAC use. This was a nationwide cohort study including 19 288 users of DOACs in 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Beyond the cardiovascular safety profile, another source of possible concerns for macrolides use in AF patients with COPD is the possible presence of drug interactions. Indeed, macrolides are a well-known class of CYP3A4 and p-glycoprotein inhibitors and may perturbate the plasma concentration of both vitamin-K antagonists and NOACs [23]. In our study, we showed that not only the risk of cardiovascular events, but also the hemorrhagic risk was reduced in azithromycin users, and this was irrespective of the type of oral anticoagulant (warfarin or NOACs).…”
Section: Discussionsupporting
confidence: 56%
“…Beyond the cardiovascular safety profile, another source of possible concerns for macrolides use in AF patients with COPD is the possible presence of drug interactions. Indeed, macrolides are a well-known class of CYP3A4 and p-glycoprotein inhibitors and may perturbate the plasma concentration of both vitamin-K antagonists and NOACs [23]. In our study, we showed that not only the risk of cardiovascular events, but also the hemorrhagic risk was reduced in azithromycin users, and this was irrespective of the type of oral anticoagulant (warfarin or NOACs).…”
Section: Discussionsupporting
confidence: 56%
“…Among this group of antibiotics, delafloxacin did not demonstrate any clinically significant impact on the QT/QTc interval in several studies [34,35] According to the latest studies, fluoroquinolones and DOAC (direct oral anticoagulants) may moderately increase the risk of bleeding by increasing systemic levels of DOAC. Investigators Tatsuya Yagi and Buster Mannheimer specify that 26 out of 9783 patients (0.27%) had bleeding events in the concomitant use window and 0.6% in the extended window of 30 days [36].…”
Section: Fluoroquinolonesmentioning
confidence: 99%